Perlindungan Hukum Notaris dalam Membuat Perjanjian Kredit Fiktif pada Perkara Tindak Pidana Korupsi - Tri Puspa Wangi; Rachmadi Usman (Lembaga Yasin AlSys, 2026)
Although criminal liability and legal protection for notaries have received attention in various previous studies, studies that specifically discuss the limits of notarial criminal liability in the preparation of credit agreement deeds based on falsified documents in corruption cases, as well as legal protection for notaries regarding the truth of the legal identity of debtors in the banking sector, remain limited. This study aims to analyze the criminal liability of notaries for deeds prepared based on falsified documents submitted by fictitious debtors and to examine forms of legal protection for notaries in the practice of bank credit provision. This study used a qualitative approach with a normative legal research design through a statutory approach, conceptual approach, and case approach. Primary, secondary, and tertiary legal materials were collected through literature study and documentation, and were then analyzed prescriptively using legal interpretation techniques. The results showed that, in principle, notaries are only responsible for the formal truth of the deeds they prepare and are not obliged to guarantee the material truth of documents or statements provided by the parties. Therefore, notaries cannot be held criminally liable in fictitious credit cases that cause state losses as long as there is no evidence of intent (mens rea), active involvement, or benefits obtained from the criminal act. This study also found that legal protection for notaries has been regulated through the mechanism of the Notary Honorary Council, the right of refusal, and the principle of due process of law, but its implementation remains suboptimal, thereby potentially leading to the criminalization of the notarial profession. These findings contribute to the development of studies on notarial law, banking law, and corruption criminal law, while also expanding understanding of the limits of notarial responsibility in bank credit transactions. The conclusion of this study emphasizes the importance of distinguishing between the formal responsibility of notaries and the material responsibility of banking institutions and debtors in fictitious credit cases. The implications of this study include theoretical contributions to the development of the concept of legal protection for the notarial profession, as well as practical implications for policymakers, law enforcement officials, banking institutions, and the Notary Honorary Council in strengthening legal certainty and preventing the criminalization of notaries who carry out their duties in accordance with legal provisions.